Estimating Benzene Exposure Level over Time and by Industry Type through a Review of Literature on Korea - Donguk Park; Sangjun Choi; Kwonchul Ha; Hyejung Jung; Chungsik Yoon; Dong-Hee Koh; Seunghun Ryu; Soogeun Kim; Dongmug Kang; Kyemook Yoo (Elsevier, 2015)
The major purpose of this study is to construct a retrospective exposure assessment for benzene through a review of literature on Korea. Airborne benzene measurements reported in 34 articles were reviewed. A total of 15,729 individual measurements were compiled. Weighted arithmetic means [AM(w)] and their variance calculated across studies were summarized according to 5-year period intervals (prior to the 1970s through the 2010s) and industry type. Industries were classified according to Korea Standard Industrial Classification (KSIC) using information provided in the literature. We estimated quantitative retrospective exposure to benzene for each cell in the matrix through a combination of time and KSIC. Analysis of the AM(w) indicated reductions in exposure levels over time, regardless of industry, with mean levels prior to the 1980-1984 period of 50.4 ppm (n = 2,289), which dropped to 2.8 ppm (n = 305) in the 1990-1994 period, and to 0.1 ppm (n = 294) in the 1995-1999 period. There has been no improvement since the 2000s, when the AM(w) of 4.3 ppm (n = 6,211) for the 2005-2009 period and 4.5 ppm (n = 3,358) for the 2010-2013 period were estimated. A comparison by industry found no consistent patterns in the measurement results. Our estimated benzene measurements can be used to determine not only the possibility of retrospective exposure to benzene, but also to estimate the level of quantitative or semiquantitative retrospective exposure to benzene.